We, as citizens of Singapore, pledge ourselves to forget - Aik, Dora Zhen Yan (Nanyang Technological University, 2020)
“We, as citizens of Singapore, pledge ourselves to forget” seeks to, on the most fundamental level, create an alternate Singapore narrative through completely made-up objects. Drawing mostly from the way of life of Singaporeans in the 70s and cultural objects from around the world, the work offers a look into the life of an average citizen in a Singapore where politicians are ever changing and chaos abounds.